Out-of-country voting systems and Egyptian elections: a future outlook - El-Saeed, Sherine Mohamed (AUC Knowledge Fountain, 2012)
The 25 January revolution has created a new reality in Egypt. It has made Egyptian citizens more eager than ever to participate in the political life and to exercise their long awaited right to elect their representatives and leaderships. It was therefore inevitable for Egyptians living abroad to demand their right to vote. The Supreme Judicial Committee for Elections (SJCE) accordingly approved a system for out-of-country voting that was implemented in the Parliamentary Elections 2011/2012. â Postal Voting' was chosen for the process. The Committee's choice of the voting system was done in an exceptionally short period of time and under considerable pressure. It was therefore crucial to examine the system that has already been adopted and implemented. It was also vital to decide which of the four main external voting options (Postal â Personal â Proxy - Electronic), or which combination of them, is the most suitable for the future Egyptian elections. The main objective of the research was to determine which option is the cheapest, which is the most secure and which is likely to lead to the highest turnout rates in out-of-country voting. A combination of quantitative and qualitative approaches was used in this study. Empirical analysis revealed a strong relationship between implementing postal voting and increasing turnout rates. Qualitative analysis suggested that e-voting is the cheapest voting method, while personal voting is the most secure. It was concluded that the most suitable out-of-country voting method for future Egyptian elections is the postal voting.